Metabolism in compensatory growth: VI. Effect of energy yielding substrates - Prapti Mahyuddin (Jurnal Ilmu Ternak dan Veteriner, 2002)
An experiment was designed to investigate the effect of different rates of glucose infusion into animals fed a maintenance diet supplemented with undegraded protein (HCHO-casein). Twelve Merino wether Iambs were divided into 3 treatment groups receiving different rates of glucose infusion, 10 mmolelh, 20 mmolelh and 30 mmolelh. The intake and digestibility of dry matter were not affected by glucose infusion. The infusion of glucose increased N retention by reducing both faecal and urinary N. It was estimated that per unit of glucose infused, animal retained 0.15 g N/mmole glucoselh. The efficiency of N retention were 28%, 35% and 44% for glucose infusion rate of 10 mmolelh, 20 mmolelh and 30 mmolelh respectively. Urea entry rate decreased as glucose infusion rate increased. The estimation of protein spared by glucose infusion calculated from N retention and urinary excretion rate gave a value of 20 g and 25 g per 100 g glucose infused respectively. The proportion of glucose entry rate (GER) that could potentially derived from amino acids reduced as the rate of glucose infusion increased, being 21%, 17% and 14% for 10 mmolelh, 20 mmolelh and 30 mmolelh of glucose infused respectively. The GER, percentage of glucose oxidized and its contribution to CO2 production increased as the rate of glucose infusion increased. However, CO2 entry rate was not significantly affected by rates of glucose infusion. Glucose uptake by the hind-limb muscles increased with increasing rates of glucose infusion and strongly related with both GER and plasma insulin concentration. There was a tendency for circulating essential amino acids to reduce as the rate of glucose infusion increased, and was more prominent for branched chain amino acids (BCAA) at 30 mmolelh of glucose infusion. The reduction of amino acids in the blood circulation occurred concurrently with the reduction in plasma urea concentration and urea entry rate indicated increased net incorporation of amino acids into protein. Key words: Compensatory growth, glucose, N retention, amin acid